Device-therapy in chronic heart failure: cardiac contractility modulation versus cardiac resynchronization therapy - Yücel, Gökhan; Gaasch, Leo; Kodeih, Abbass; Hetjens, Svetlana; Yazdani, Babak; Pfleger, Stefan; Dürschmied, Daniel; Abraham, William T.; Akın, Ibrahim; Kuschyk, Jürgen (ESC heart failure, 2025)
Aims Cardiac implantable electrical devices such as cardiac resynchronization therapy with defibrillator (CRT-Ds) or cardiac contractility modulation (CCMs) are therapy options for patients with symptomatic heart failure (HF) and reduced left ventricular ejection fraction (LVEF) despite optimal medical treatment. As yet, a comparison between both devices has not been performed. Methods and results The Mannheim Cardiac Resynchronization Therapy Registry (MARACANA) and the Mannheim Cardiac Contractility Modulation Observational Study (MAINTAINED) included all patients who received CRTs or CCMs in our medical centre between 2012 and 2021. For the present analysis, we retrospectively compared patients provided with either CRT-Ds (n = 220) or CCMs with additional defibrillators (n = 105) regarding New York Heart Association classification (NYHA), LVEF, tricuspid annular plane systolic excursion (TAPSE), QRS-width and other HF modification aspects after 12 months. Before implantation, CCM patients presented with lower LVEF (23.6 ± 6.2 vs. 26.3 ± 6.5%) and worse NYHA (3.03 ± 0.47 vs. 2.81 ± 0.48, both P < 0.05), compared with CRT-D patients. Follow-up improvements in NYHA (2.43 ± 0.67 vs. 2.28 ± 0.72), LVEF (30.5 ± 10.7 vs. 35.2 ± 10.5%) and TAPSE (17.2 ± 5.2 vs. 17.1 ± 4.8 to 18.9 ± 3.4 vs. 17.3 ± 3.6 mm, each P < 0.05) were comparable. The intrinsic QRS-width was stable with CCM (109.1 ± 18 vs. 111.7 ± 19.7 ms, P > 0.05), while the paced QRS-width with CRT-D after 12 months was lower than intrinsic values at baseline (157.5 ± 16.5 vs. 139.2 ± 16 ms, P < 0.05). HF hospitalizations occurred more often for CCM than CRT-D patients (45.7 vs. 16.8%/patient years, odds ratio 4.2, P < 0.001). Conclusions Chronic heart failure patients could experience comparable 12-month improvements in functional status and ventricular reverse remodelling, with appropriately implanted CCMs and CRT-Ds. Differences in HF hospitalization rates may be due to the more advanced HF of CCM patients at implantation.